A CFD–based evaluation of selective non–catalytic reduction of nitric oxide in iron ore grate–kiln plants. (1st January 2015) - Burström, Per E.C.; Antos, Dorota; Lundström, T. Staffan; Marjavaara, B. Daniel
The overall goal of this study is to explore the function of selective non–catalytic reduction of nitric oxide (NO) in iron ore grate–kiln plants. Computational fluid dynamics is used to model the flow and the injection of urea and cyanuric acid reagents. Temperature, residence time and inlet NO content are varied, and the effects on the reduction of NO are studied. The simulations show that the use of urea results in a higher reduction of NO within the temperature window investigated as compared to cyanuric acid; however, urea cannot be used for NO reduction over the entire range of applicable temperatures. Cyanuric acid is usable within the entire temperature range for high NO content (i.e., 300 ppm) in the flue gas, but it is not effective for low NO concentration (i.e., 150 ppm). Moreover, the simulations indicate that temperature has a larger influence on the NO reduction than the residence time.